PELAKSANAAN DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK DI WILAYAH HUKUM KEPOLISIAN RESOR AGAM - Yulisa Fitri; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Until now, criminal acts committed by children still occur in the jurisdiction ofAgam Police Force. In accordance with Law No. 11 Year 2012 on the CriminalJustice System of Children the process of settlement of child criminal cases that isthrough diversi. Criminal acts committed by children in the territory of AgamPolice Force in 2015 as many as 5 cases, in 2016 as many as 5 cases, and in 2017the number of crimes committed by children as many as 6 cases. From the abovecases, 4 cases have been successfully diverted, 7 cases failed to be resolved bydiversion while 5 cases were not attempted to be diverted.This research is a type of research that is empirical or sociological lawresearch. Legal juridical empirical research or sociological law research isresearch conducted directly on site or in the field to obtain data to provide acomplete and clear picture of the problem under study. Viewed from its naturedescribes the facts of symptoms and facts contained in life in a deep social.The results of research conducted by the author is the firstimplementation of the diversion in the process of criminal justice of childrenhandled by the Police Resort Agam not optimal. Second, constraints from the lackof knowledge and legal awareness of the community, at least the number ofmembers of the Women and Child Protection unit and not yet holds a law degree.Third, efforts to overcome these obstacles by increasing participation andknowledge with legal socialization to the community, increasing the number ofmembers of the Protection of Women and Children unit and should have a policedegree holds law degree.Keywords: Investigation - Child Crime - Diversi